In-situ long-period monitoring of suspended particulate matter dynamics in deep sea with digital video images - Wang, Hui; Hu, Cong; Feng, Xuezhi; Ji, Chunsheng; Jia, Yonggang (Frontiers in Marine Science, 2022)
Suspended particulate matter (SPM) plays an important role in material transport, deposition, resuspension and the function of benthic communities’ processes in deep sea. SPM concentration data is usually indirectly measured by optical/acoustic sensors. However, converting these sensors’ signal to SPM concentration is associated with a number of uncertainties, which will lead to mis-estimation of the results. Some researchers recommend combining several optical/acoustic sensors to determine SPM concentration. However, due to the lack of corresponding video images, the interpretation of significant mismatch signals recorded by different sensors is subjective. Consequently, a better understanding of long-period SPM dynamics, especially in deep sea, is still a challenge. In this study, we seek to monitor the dynamics of SPM in deep sea, by firstly obtaining in-situ digital video images at a water depth of 1450 m on the northern slope of South China Sea in 2020, and secondly developing a digital image processing method to process the in-situ monitoring data. In this method, we defined an image signal which was the ratio between the area of the SPM and that of the total image, to characterize the SPM concentration. A linear regression model of the image signal and SPM concentration was established (R2 = 0.72). K-fold cross-validation showed that the performance of the model was well. We calculated the SPM concentration derived from image signal, and manually classified SPM into three distinct morphological groups. The long-period observation revealed that numerous aggregates existed in deep sea. The change of SPM concentration and morphology under hydrodynamics was synchronous. When current speed equaled to or exceeded 0.15 m/s, there was a significantly increase in SPM concentration and size. However, such increase was episodic. When current speed decreased, they will also decrease. In addition, we compared the image signal with the optical/acoustic backscattering signal, analyzed the mismatch period among these three signals. We found that the optical backscatter signal can’t accurately reflect the SPM concentration during the mismatch period. To our best knowledge, this is the first time that the in-situ digital video images were used to analyze the dynamics of SPM in deep sea.